Structural and Functional Analysis of Nonheme Iron Enzymes BCMO-1 and BCMO-2 from Caenorhabditis elegans - Pan, Weimin; Zhou, Yong-Ling; Wang, Jian; Dai, Huai-En; Wang, Xiao; Liu, Lin (Frontiers in Molecular Biosciences, 2022)
Carotenoid metabolism is critical for diverse physiological processes. The genome of nematode Caenorhabditis elegans has two genes annotated as β-carotene 15,15′-monooxygenase (BCMO), but the function of BCMO-1 and BCMO-2 remains uncharacterized. Sequence homology indicates that the two enzymes belong to the carotenoid cleavage dioxygenase family that share a seven-bladed β-propeller fold with a nonheme iron center. Here we determined crystal structures of BCMO-1 and BCMO-2 at resolutions of 1.8- and 1.9-Angstrom, respectively. Structural analysis reveals that BCMO-1 and BCMO-2 are strikingly similar to each other. We also characterized their β-carotene cleavage activity, but the results suggest that they may not act as β-carotene 15,15′-oxygenases.